PROSPECTS OF DEVELOPMENT OF AN INVESTment and BUILDING COMPLEX - A. Kozlovsky; N. Moiseenko (Вестник университета)
In the article some key questions of reproduction of fixed capital and maintenance of the given process with financing sources are considered. The current situation estimation in investment and building sphere of economy is given and ways of the decision of the basic problems of investment activity to building branch are planned.